Dynamic programming approach to achieve higher view-count for YouTube videos. (28th March 2023) - Irshad, Mohammed Shahid; Anand, Adarsh; Roy, Sankar Kumar
Broadcast media telecasts their programs at fixed timing, which forces the viewer to be presented at the time of broadcast whereas online streaming platforms allows viewers to watch videos any time. YouTube being the free streaming platform attracts lot of viewers where short videos are uploaded. With its growing popularity content creators have started uploading series of scripted or non-scripted content (video) in episode forms known as a web series. A web series usually has 5-10 episodes, and each episode is uploaded independently. The producers desire maximum view-counts with minimum promotional expenditure on each web series. This paper presents an optimisation modelling framework for budget allocation in order to achieve a greater number of view-counts. The proposed framework takes into consideration the aspiration level for the episodes wherein; dynamic programming approach has been utilised to numerically illustrate the validation on two web series on YouTube.